U.S. and China: Hard and Soft Power Potential - Łoś, Robert (International Studies. Interdisciplinary Political and Cultural Journal, 2018)
The United States, as a leading world power, has to face China – an emerging powerful rival. The potential of both states’ power is measured by universal indicators. On a military level, these indicators are: military expenditure, soldiers/reserve/soldiers abroad, offensive weapons, nuclear warheads. On an economic level: GDP value, reserve currency/public debt to GNP, direct investment home and abroad. With regard soft power, six categories have been taken into consideration: diplomacy, socio-political, socio-economic, education, high and popular culture. All of the three researched levels were correlated with both states’ political system specificity and the character of the international arena’s relations. It allowed for the assessment of the current levels of both states’ power as well as their future prospects.